Short fiber carbon carbon composite HJT bearing frame and preparation method thereof

CN119430980BActive Publication Date: 2026-10-13HANGZHOU KAIKEN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411709443.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2026-10-13
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

[0003]目前碳碳复合材料主要是采用碳布浸胶、铺层压制或采用针刺工艺制造,制造周期长,且长碳纤维存在明显的各向异性,不同方向的性能差异明显

Benefits of technology

[0026]本发明提供的技术方案,与已知的公有技术相比,具有如下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155294220000041
    Figure BDA0005155294220000041
  • Figure BDA0005155294220000051
    Figure BDA0005155294220000051
  • Figure HDA0005155294230000011
    Figure HDA0005155294230000011
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, in particular to a short fiber carbon-carbon composite HJT bearing frame and a preparation method thereof, wherein the short fiber carbon-carbon fibers manufactured by the process are more uniformly dispersed, isotropic in XY direction, and the stress on each region of the short fiber carbon-carbon after bearing is more uniform. The technical solution of the present application is simple to operate, requires less equipment investment, and has a short manufacturing cycle; and can meet the requirements of mass production, low cost and rapid manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, and in particular to a short-fiber carbon-carbon composite HJT load-bearing frame and its preparation method. Background Technology

[0002] Carbon-carbon composite materials are widely used in aerospace, photovoltaic and other fields due to their excellent high temperature resistance, low coefficient of thermal expansion, high strength and modulus at high temperatures.

[0003] Currently, carbon-carbon composite materials are mainly manufactured using carbon cloth impregnation, layup pressing, or needle punching processes. These methods have long manufacturing cycles, and the long carbon fibers exhibit significant anisotropy, with noticeable performance differences in different directions. Current methods for preparing carbon-carbon composite products involve weaving long carbon fibers into fabrics or needle punching them into 2.5D preforms. These products have poor processing performance, uneven surfaces, and cannot be coated with uniform ceramic coatings, failing to meet the requirements for load-bearing frames in the HJT process. Summary of the Invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a short fiber carbon-carbon composite HJT load-bearing frame and its preparation method, which can effectively solve the above-mentioned problems of the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A method for preparing a short-fiber carbon-carbon composite HJT support frame, the preparation process of the short-fiber carbon-carbon composite HJT support frame includes the following steps:

[0007] S1: Raw material preparation and fiber dispersion: Carbon fiber is first cut into short fibers of different lengths according to a certain length range, and then subjected to high temperature treatment;

[0008] S2: Short carbon fiber cloth is obtained by mixing short-cut carbon fibers of different lengths in a certain weight ratio and dispersing them through airflow.

[0009] S3: Material placement: Evenly place the short carbon fiber cloth onto the lower mold of the mold;

[0010] S4: Adhesive pouring: Pour the adhesive evenly onto the surface of the laid short carbon fiber cloth, and then let it stand.

[0011] S5: Curing: Curing is performed;

[0012] S6: Carbonization and densification: Carbonization is performed, followed by gas phase densification, and then high-pressure liquid phase densification and curing are carried out using resin.

[0013] S7: High-temperature carbonization: Further carbonization is carried out after densification;

[0014] S8: Machining: Obtaining carbon-carbon composite materials of the required dimensions through machining;

[0015] S9: Coating spraying: Finally, a yttrium oxide ceramic coating is sprayed onto the surface of the carbon-carbon composite material.

[0016] In step S1, the lengths of the carbon fibers obtained after short cutting are 25-35mm, 45-55mm, and 100-110mm, respectively; the temperature of the high-temperature treatment is 900-1000℃.

[0017] In step S2, the mass ratio of the three different lengths of short-cut carbon fibers is: 25-35mm: 45-55mm: 100-110mm = (1-2): (5-5.5): (1-2); the parameter control during the airflow dispersion process is: input air volume: 0.2-0.5m³. 3 Dispersion speed: 500-1000 r / min, dispersion time: 30-60 min.

[0018] In step S3, the mold includes an upper mold, a lower mold, and stops. The product thickness is controlled by the four stops. By changing the stops, products of different thicknesses can be manufactured.

[0019] In step S4, the adhesive is a mixture of liquid phenolic resin with 50%-60% residual carbon and 1000-mesh graphite powder, with a mass ratio of 100:(10-15); the mass ratio of adhesive to carbon fiber is (4-5):7.

[0020] In step S5, the curing method is: (45-50)℃ / (1-2)h+(120-125)℃ / 1-2h+(150-155)℃ / (2-3)h.

[0021] In step S6, the carbonization treatment temperature is 900-1600℃, and the holding time is 2-4 hours; the carbon source gas used in the gas-phase densification is methane, the temperature is 1000-1500℃, the time is 50-200 hours, the pressure is 4-10 kPa, the heating rate is 50-600℃ / h, and the gas flow rate is 5-15 m³ / h. 3 / h; The resin used in the liquid phase densification is furfuryl ketone resin, with a high pressure of 2.0-5.0 MPa, and the curing method is: (125-135)℃ / (1-2)h + (175-185)℃ / (3-4)h

[0022] In step S7, the carbonization temperature is 1600-2000℃, and the holding time is 4-6 hours.

[0023] In step S9, during the spraying process, plasma spraying is used. The particle size of the yttrium oxide powder is 10-50 μm. Other gases used in the plasma spraying process include argon and hydrogen. The flow rate of argon is 30-50 slpm, the flow rate of hydrogen is 5-10 slpm, the flow rate of the argon carrier gas is 2-5 slpm, the powder feeding rate is 25-50 g / min, the spraying distance is 100-150 mm, and the thickness of the yttrium oxide ceramic coating after spraying is 100-200 μm with a roughness ≤10 μm.

[0024] The short-fiber carbon-carbon composite HJT load-bearing frame is prepared by the above preparation method.

[0025] Beneficial effects

[0026] The technical solution provided by this invention has the following advantages compared with known public technologies:

[0027] 1. This invention produces short fibers by cutting and dispersing long fibers, resulting in products that are isotropic in the X and Y directions and have excellent processability.

[0028] 2. The surface smoothness and roughness after processing are superior to those of long fiberboard, which has a significant advantage for subsequent ceramic coating on the product surface.

[0029] 3. The short-fiber carbon fiber manufactured according to this scheme has a short manufacturing cycle, high pass rate, and simple densification process. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0031] Figure 1 This is a short-fiber carbon-carbon composite material HJT load-bearing frame mold.

[0032] Figure 2 This is a flowchart illustrating the preparation method of a short-fiber carbon-carbon composite HJT load-bearing frame.

[0033] Figure 3 This is a photograph of the surface condition of the final HJT bearing frame. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0035] The present invention will be further described below with reference to embodiments.

[0036] 1. Raw material preparation: Use a filament cutter to cut T700 grade 3k or 12k carbon fibers into short sections. The fiber lengths are cut into sections of 30mm, 50mm, and 100mm. The cut carbon fibers are then subjected to high-temperature treatment at 950℃ for 2 hours to remove the sizing agent from the surface.

[0037] 2. Fiber dispersion: Short-cut carbon fibers are mixed in a weight ratio of 30mm:50mm:100mm = 1.5:5:1.5, and then placed into an airflow disperser for uniform dispersion and combing to produce short fiber cloth. The short fiber cloth has a basis weight of 230gsm and a width of 1800mm. The airflow dispersion parameters are: input air volume: 0.3m3 / min, dispersion speed: 800r / min, and dispersion time: 50min.

[0038] 3. Preparation of impregnation solution: Mix liquid phenolic resin with 55% residual carbon and 1000 mesh graphite powder at a weight ratio of 100:12. Mix at 30℃, 300 rpm, and for 0.8 hours. Stir until the viscosity of the mixed resin is 400 mPa·s. Add graphite powder gradually during the stirring process. Prepare a total of 4.5 kg of impregnation solution.

[0039] 4. Mold preparation: Design the mold according to the product shape and thickness. The mold consists of an upper mold, a lower mold and a stop block. In this embodiment, the product size is 2000*1000*3mm.

[0040] 5. Material laying: Evenly and completely lay the dispersed short carbon fiber cloth onto the lower mold, with a laying amount of 2100*1100*4.5mm for a 6.5kg preform;

[0041] 6. Resin pouring: Pour the prepared 4.5kg of resin evenly onto the surface of the laid material, and let it stand for 20 minutes after the resin pouring is completed;

[0042] 7. Pressing and curing: After standing, start the press curing program: 50℃ / 1h + 120℃ / 1h + 150℃ / 2h, and gradually increase the curing pressure from 0MPa to 5MPa.

[0043] 8. Carbonization: Take out the cured product and place it in a carbonization furnace for carbonization treatment. The carbonization temperature is 1200℃ and the carbonization holding time is 3 hours.

[0044] 9. Vapor Phase Densification: The carbonized product is placed in a CVD furnace for vapor phase densification. Methane is used as the carbon source gas. The process temperature is 1200℃, the process time is 100h, the process pressure is 6kPa, the heating rate is 300℃ / h, and the gas flow rate is 10m³ / h. 3 / h;

[0045] 10. Liquid phase densification: The product is subjected to high-pressure liquid phase densification using furfuryl ketone resin, followed by curing at 130℃ / 2h + 180℃ / 3h.

[0046] 11. High-temperature carbonization: Take out the impregnated and densified product and place it in a carbonization furnace for carbonization. The carbonization temperature is 1800℃ and the carbonization holding time is 5 hours.

[0047] 12. Machining: Machining is performed on the densified product to obtain carbon-carbon composite material products of the corresponding dimensions;

[0048] 13. Coating Spraying: A yttrium oxide ceramic coating is uniformly sprayed onto the product surface using plasma spraying technology. The particle size of the yttrium oxide powder is 30 μm, the plasma gas argon flow rate is 40 slpm, the plasma gas hydrogen flow rate is 8 slpm, the powder carrier gas argon flow rate is 3 slpm, the powder feeding rate is 35 g / min, the spraying distance is 120 mm, the thickness of the yttrium oxide ceramic coating is 150 μm, and the roughness is 8 μm.

[0049] Comparative Example 1:

[0050] The procedure was carried out according to the method in Example 1, except that the length and ratio of the short fibers after the carbon fiber was cut in the first step were 70mm:90mm = 1:2.

[0051] Comparative Example 2:

[0052] The procedure was carried out according to the method in Example 1, except that a conventional phenolic resin was used in the liquid phase densification step, with a resin carbon residue of less than 50%.

[0053] Comparative Example 3:

[0054] The method described in Example 1 was followed, except that the CVD vapor phase densification process step was omitted, and only liquid phase densification was used.

[0055] Comparative Example 4:

[0056] The process is carried out according to the method in Example 1, except that existing long fibers are used as raw materials for the processing.

[0057] Test Results

[0058]

[0059]

[0060] Referring to Example 1 and Comparative Example 1, it can be seen that the load-bearing frame made according to the length and weight ratio in Example 1 has better bending performance.

[0061] Referring to Example 1 and Comparative Example 2, it can be seen that the density of Comparative Example 2 is reduced.

[0062] Referring to Example 1 and Comparative Example 3, it can be seen that the bearing frame made in Comparative Example 3 has a rougher surface, poorer bending performance, and lower density.

[0063] Referring to Example 1 and Comparative Example 4, it can be seen that if existing long fibers are used as the processing technology, it is obviously impossible to meet the requirements of carbon-carbon composite materials for the load-bearing frame in the HJT process. The product has poor processing performance, uneven surface, and anisotropy in the XY direction.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame, characterized in that, The preparation process of the short-fiber carbon-carbon composite HJT load-bearing frame includes the following steps: S1: Raw material preparation and fiber dispersion: Carbon fiber is first cut into short fibers of different lengths according to a certain length range, and then subjected to high temperature treatment; the lengths of the carbon fibers obtained after cutting are 25-35mm, 45-55mm, and 100-110mm respectively. S2: Short carbon fiber of different lengths after shavings are mixed in a certain weight ratio and dispersed by airflow to obtain short carbon fiber cloth; the mass ratio of the three different lengths of short carbon fiber is: 25-35mm: 45-55mm: 100-110mm = (1-2): (5-5.5): (1-2); S3: Material placement: Evenly place the short carbon fiber cloth onto the lower mold of the mold; S4: Adhesive casting: The adhesive is evenly cast onto the surface of the laid short carbon fiber cloth and then left to stand; the adhesive is a mixture of liquid phenolic resin with 50%-60% residual carbon and 1000 mesh graphite powder, with a mass ratio of 100:(10-15); the mass ratio of adhesive to carbon fiber is (4-5):

7. S5: Curing: Curing is performed; the curing method is: (45-50)℃ / (1-2)h+(120-125)℃ / (1-2)h+(150-155)℃ / (2-3)h; S6: Carbonization and densification: Carbonization is performed, followed by gas phase densification, and then high-pressure liquid phase densification and curing are carried out using resin. S7: High-temperature carbonization: Further carbonization is carried out after densification; S8: Machining: Obtaining carbon-carbon composite materials of the required dimensions through machining; S9: Coating spraying: Finally, a yttrium oxide ceramic coating is sprayed onto the surface of the carbon-carbon composite material.

2. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S1, the temperature of the high-temperature treatment is 900-1000℃.

3. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S2, the parameters for the airflow dispersion process are controlled as follows: input air volume: 0.2-0.5 m³ / s. 3 Dispersion speed: 500-1000 r / min, dispersion time: 30-60 min.

4. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S3, the mold includes an upper mold, a lower mold, and stops. The product thickness is controlled by the four stops. By changing the stops, products of different thicknesses can be manufactured.

5. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S6, the carbonization temperature is 900-1600℃, and the holding time is 2-4 hours; the carbon source gas used in the gas-phase densification is methane, the temperature is 1000-1500℃, the time is 50-200 hours, the pressure is 4-10 kPa, the heating rate is 50-600℃ / h, and the gas flow rate is 5-15 m³ / h. 3 / h; The resin used in the high-pressure liquid phase densification is furfuryl ketone resin, with a pressure of 2.0-5.0 MPa, and the curing method is: (125-135)℃ / (1-2)h+(175-185)℃ / (3-4)h.

6. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S7, the carbonization temperature is 1600-2000℃, and the holding time is 4-6 hours.

7. The method for preparing a short-fiber carbon-carbon composite HJT load-bearing frame according to claim 1, characterized in that, In step S9, during the spraying process, plasma spraying is used. The particle size of the yttrium oxide powder is 10-50 μm. The gases used in the plasma spraying process include argon and hydrogen. The flow rate of argon is 30-50 slpm, the flow rate of hydrogen is 5-10 slpm, the flow rate of the argon carrier gas is 2-5 slpm, the powder feeding rate is 25-50 g / min, the spraying distance is 100-150 mm, and the thickness of the yttrium oxide ceramic coating after spraying is 100-200 μm with a roughness ≤10 μm.

8. A short-fiber carbon-carbon composite HJT load-bearing frame, characterized in that, The short-fiber carbon-carbon composite HJT load-bearing frame is prepared by the method described in any one of claims 1 to 7. The short-fiber carbon-carbon composite HJT load-bearing frame has a bending performance greater than or equal to 45 GPa and a density greater than or equal to 1.5 g / cm³. 3 .

Citation Information

Patent Citations

  • Method for preparing ablation-resistant coating

    CN107021787A

  • Preparation method of carbon / carbon PECVD bearing frame

    CN118459241A

  • PECVD (plasma enhanced chemical vapor deposition) bearing frame and preparation method thereof

    CN118724603A